Emergent ultrafast phenomena in correlated oxides and heterostructures. (31st January 2017) - Gandolfi, M; Celardo, G L; Borgonovi, F; Ferrini, G; Avella, A; Banfi, F; Giannetti, C
Abstract: The possibility of investigating the dynamics of solids on timescales faster than the thermalization of the internal degrees of freedom has disclosed novel non-equilibrium phenomena that have no counterpart at equilibrium. Transition metal oxides (TMOs) provide an interesting playground in which the correlations among the charges in the metal d -orbitals give rise to a wealth of intriguing electronic and thermodynamic properties involving the spin, charge, lattice and orbital orders. Furthermore, the physical properties of TMOs can be engineered at the atomic level, thus providing the platform to investigate the transport phenomena on timescales of the order of the intrinsic decoherence time of the charge excitations. Here, we review and discuss three paradigmatic examples of transient emerging properties that are expected to open new fields of research: (i) the creation of non-thermal magnetic states in spin–orbit Mott insulators; (ii) the possible exploitation of quantum paths for the transport and collection of charge excitations in heterostructures; (iii) the transient wave-like behavior of the temperature field in strongly anisotropic TMOs.